Colour atlas of trees and woody plants - Bowes, Bryan G. (Boca Raton, FL : CRC Press, 2020)
Trees and plants are important components of the human environment havingsignificant presence beyond agricultural and recreational values. Colour Atlas of Woody Plants and Trees presents a photographic compilation of morphological features of trees and shrubs giving attention to their unique aspects not presented in existing books. By increasing awareness to users through high quality, full-color photographs and informative text, this book demonstrates the enormous diversity of vascular trees and plants living today. Features: Full color atlas offers concise, but highly informative text accompanied by over 200 high-resolution digital tree images Contains images of the anatomy of tree structures and evolution of the most important features of trees Presents information on the varied structure and morphology exhibited by trees and demonstrates their vital importance in the current struggle for the survival of our human society Surveys the most important morphological features of plants, shrubs and trees Presents aspects of plants and trees both common and rarely seen in nature Bryan Geoffrey Bowes is a retired Senior Lecturer in the Botany Department at Glasgow University and was a Research Fellow in ETH Zurich, Harvard University, and University of New England, Australia. His research interests encompass plant anatomy and ultrastructure, plant regeneration, and morphogenesis in vitro.
OCLC-licensed vendor bibliographic record.
Keywords: Trees -- Atlases; Woody plants -- Atlases; NATURE / Ecology; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General